Contribution of cold fronts to seasonal rainfall in simulations over the southern la Plata Basin - De Jesus, Eduardo Marcos; Da Rocha, Rosmeri Porfï¿½rio; Reboita, Michelle Simï¿½es; Llopart, Marta [UNESP]; Dutra, Lï¿½via Mï¿½rcia Mosso; Remedio, Armelle Reca C. (Inter-Research Science Center, 2016)
This work investigates how regional climate models REMO and RegCM4 simulate the frequency of cold fronts (CFs) over southern Brazil and the contribution of these systems to the seasonal precipitation over the southern part of La Plata Basin (SLPB) in South America. Simulations were driven by the ERA-Interim reanalysis and compared with local observations (from Rio Grande station; RG), ERA-Interim, and rainfall analysis from the Climate Prediction Center (CPC). CF identification was carried out objectively by considering (1) the turning of the meridional wind component from north to south and (2) a decrease in air temperature between 1 d before and 1 d after the CF passage. For the period 1991-2008, a mean of 55.3, 53.1 and 51.8 CFs yr-1 were identified, respectively, for RG (observed), REMO and RegCM4. These values show a small bias in the simulated annual frequency of CFs (around -5%), but the underestimation reaches -17% during summer in the RegCM4. In the simulations, it is possible to find some association between seasonal bias of rainfall and the bias of rainfall during CF periods (defined as extending from 2 d before to 2 d after the CF passage) over SLPB. Except in summer, RegCM4 presents stronger biases than REMO for rainfall for both CF periods and overall seasonal climatology. For the winter season, the CF composites indicate that deeper low pressure and larger availability of moisture at low levels (from 2 d before to the day of the CF) contribute to the small underestimation of rainfall in REMO (-5%) compared with RegCM4 (-25%).
Keywords: Cold fronts; La Plata Basin; Precipitation; Regional climate models